Effect of semaglutide on arrhythmic, major cardiovascular, and microvascular outcomes in patients with type 2 diabetes: a systematic review and meta-analysis - Wu, Rui; Xing, Bo; Huang, Yuting; Zhou, Zijun; Sun, Boxuan; Yu, Liming; Wang, Huishan (Frontiers in Endocrinology, 2025)
BackgroundSemaglutide, a glucagon-like peptide-1 (GLP-1) receptor agonist, has shown promise in managing hyperglycemia and reducing cardiovascular (CV) outcomes. However, its effects on arrhythmic, major CV, and microvascular outcomes remain uncertain. This systematic review and meta-analysis aimed to evaluate these outcomes in patients with type 2 diabetes (T2D) treated with semaglutide.MethodsWe searched the PubMed, Embase, and Cochrane databases for eligible randomized controlled trials (RCTs) reported up to November 2024. We performed a meta-analysis via a random-effects model to estimate overall relative risks (RRs) with 95% confidence intervals (CIs) for arrhythmic, major CV, and microvascular outcomes. We conducted subgroup analyses on the basis of different administration types, treatment comparisons, and treatment durations. Additionally, we performed a meta-regression for retinopathy complications on the basis of baseline patient characteristics.ResultsThis meta-analysis included 30 RCTs encompassing 32490 patients with T2D. Compared with the controls, semaglutide significantly reduced the incidence of atrial fibrillation (AF) (RR 0.73, 95% CI 0.54 to 0.98), complete atrioventricular (AV) block (RR 0.22, 95% CI 0.06 to 0.80), death from CV causes (RR 0.76, 95% CI 0.58 to 0.98), and revascularization (RR 0.68, 95% CI 0.52 to 0.88). Subgroup analyses revealed that semaglutide (long-term treatment) reduced the risk of AF, supraventricular tachycardia, and complete AV block. Meta-regression analysis revealed that the heterogeneity of retinopathy complications was not associated with baseline patient characteristics.ConclusionSemaglutide reduces the risk of AF, complete AV block, death from CV causes, and revascularization in patients with T2D, with long-term treatment showing greater benefits for arrhythmic outcomes.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024618146.